Automated targeting technique for single-impurity resource conservation networks. Part 2: Aingle-pass and partitioning waste-interception systems - Ng, Denny K.S. (Animo Repository, 2009)
Part 1 of this pair of articles presents an automated targeting technique to identify minimum fresh resource flow rate/cost targets in a resource conservation network (RCN) with material reuse/recycle. After the potential for conservation through direct reuse/recycle is exhausted, fresh resource consumption can be further reduced by incorporating waste-interception (regeneration) processes. Hence, the proposed automated targeting technique in part 1 of this pair of articles is extended to determine the targets for RCNs with interception placement. The waste-interception systems are modeled as treatment processes with either fixed outlet concentrations or fixed impurity load removal ratios. The approach also distinguishes between single-pass and partitioning regenerators, which have different implications for RCNs. Literature examples and industrial cases are solved to illustrate the proposed approach. © 2009 American Chemical Society.